Toxin Synthesis by Clostridium difficile Is Regulated through Quorum Signaling - Darkoh, Charles (mBio, 2015)
Clostridium difficile infection (CDI) is dramatically increasing as a cause of antibiotic- and hospital-associated diarrhea worldwide. C. difficile, a multidrug-resistant pathogen, flourishes in the colon after the gut microbiota has been altered by antibiotic therapy. Consequently, it produces toxins A and B that directly cause disease. Despite the enormous public health problem posed by this pathogen, the molecular mechanisms that regulate production of the toxins, which are directly responsible for disease, remained largely unknown until now. Here, we show that C. difficile toxin synthesis is regulated by an accessory gene regulator quorum-signaling system, which is mediated through a small (<1,000-Da) thiolactone that can be detected directly in stools of CDI patients. These findings provide direct evidence of the mechanism of regulation of C. difficile toxin synthesis and offer exciting new avenues both for rapid detection of C. difficile infection and development of quorum-signaling-based non-antibiotic therapies to combat this life-threatening emerging pathogen.